2004
DOI: 10.1089/107632704323061799
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation Does Not Impair Insulin Efficacy in Three-Dimensional Cartilage Culture: An Investigation toward Biomimetic Polymers

Abstract: A major goal in tissue engineering is the controlled application of growth factors. As a novel application system, we are currently developing biomimetic polymers that are processed into three-dimensional scaffolds. Bioactive proteins will be covalently bound to the polymers via a poly(ethylene glycol) (PEG) linker. Of paramount importance is the maintenance of the biological activity of the protein after PEGylation and covalent binding to the polymer. Therefore, within this study, insulin used as a model prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Some studies using the spacer chains were performed and the increase in the activity is reported. 26,[29][30][31][32]48 However, possible implications of steric hindrance in spacing growth factor from the substrate and the possible impact on growth factor binding to its cell surface receptor should be taken into consideration. In fact, the POE conjugation reduced the biological activity of insulin.…”
Section: Spacer Insertion and Surface Stiffnessmentioning
confidence: 99%
“…Some studies using the spacer chains were performed and the increase in the activity is reported. 26,[29][30][31][32]48 However, possible implications of steric hindrance in spacing growth factor from the substrate and the possible impact on growth factor binding to its cell surface receptor should be taken into consideration. In fact, the POE conjugation reduced the biological activity of insulin.…”
Section: Spacer Insertion and Surface Stiffnessmentioning
confidence: 99%
“…Bovine chondrocytes were harvested from knee joints by collecting fresh articular cartilage from the surfaces of the patellar grove under aseptic conditions. The cartilage was cut into small pieces and enzymatically digested by collagenase type II in cell culture medium (21). The cell digest was filtered through a 150 mm filter, centrifuged at 1,200 rpm for 5 min and washed three times with PBS.…”
Section: Determination Of the Chemical Stability Of Micronized Insulimentioning
confidence: 99%
“…A NMR spectrum of PEG is relatively straightforward to interpret as the majority of protons along the PEG backbone are in the same coupling environment and hence produce a single peak at a chemical shift of ∼3.65 ppm. NMR has also been utilized to characterize PEGylated proteins and could prove to be a useful tool in providing a quantitative assay for measuring the metabolism of PEG since it is possible to integrate all PEG moieties.…”
Section: Introductionmentioning
confidence: 99%